Nest predation by arboreal snakes on cavity nesting-birds in dry Chaco woodlands - Berkunsky, Igor (2011)
Ornithologists have extensively studied nest predation because predators are responsible for most nest failures (Ricklefs 1969, Martin 1995, Newton 1998). Factors correlated with variation in the occurrence of predation on Neotropical birds have been intensively studied and documented, but identity of predators has largely remained unknown (Larivièreon factors affecting nest success and to understand the dynamics of predator-prey relationships (Benson et al. 2010). When predators have been documented, 1999, Lahti 2009). Knowledge of the identity of predators is often necessary to accurately focus conservation efforts for threatened species as well as to interpret results of research